2007
DOI: 10.1194/jlr.m700158-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

ApoA-I cleaved by transthyretin has reduced ability to promote cholesterol efflux and increased amyloidogenicity

Abstract: A fraction of plasma transthyretin (TTR) circulates in HDL through binding to apolipoprotein A-I (apoA-I). Moreover, TTR is able to cleave the C terminus of lipid-free apoA-I. In this study, we addressed the relevance of apoA-I cleavage by TTR in lipoprotein metabolism and in the formation of apoA-I amyloid fibrils. We determined that TTR may also cleave lipidated apoA-I, with cleavage being more effective in the lipid-poor preb-HDL subpopulation. Upon TTR cleavage, discoidal HDL particles displayed a reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 29 publications
4
53
2
2
Order By: Relevance
“…ApoA-I is well-known for its antioxidant ability in both lipid-free and lipid-bound states (Cho et al, 2006). Similarly, Liz et al (2007) reported that cleavage of apoA-I (26 kDa) by transthyretin is associated with loss of unique features of dysfunctional HDL and an increase in amyloidogenicity. They showed loss of C-terminal (226-243) in apoA-I is associated with a severe decrease in the alpha-helix and an increase in beta-strands and random coils in apoA-I.…”
Section: Discussionmentioning
confidence: 99%
“…ApoA-I is well-known for its antioxidant ability in both lipid-free and lipid-bound states (Cho et al, 2006). Similarly, Liz et al (2007) reported that cleavage of apoA-I (26 kDa) by transthyretin is associated with loss of unique features of dysfunctional HDL and an increase in amyloidogenicity. They showed loss of C-terminal (226-243) in apoA-I is associated with a severe decrease in the alpha-helix and an increase in beta-strands and random coils in apoA-I.…”
Section: Discussionmentioning
confidence: 99%
“…Proteolytic products of certain intracellular events, including apoptotic and necrotic cell death (25), may also be released into the blood, where they may serve as useful markers of these processes. Proteolytic fragments of normal plasma proteins are also directly implicated in the pathogenesis of certain diseases, such as amyloidoses and atherosclerosis (26,27). Within our N-terminal peptide dataset, we find examples of all of these classes ( Table 1).…”
mentioning
confidence: 93%
“…ApoA-I was subsequently identified as the unique plasma TTR substrate (51). The relevance of apoA-I cleavage by TTR was analyzed and it was shown that it impacts on HDL biology and in the development of atherosclerosis by reducing the ability of apoA-I to promote cholesterol efflux and by increasing apoA-I amyloidogenicity (52). Nevertheless, the in vivo impact of TTR in atherosclerosis requires further investigation.…”
Section: Ttr Binding To Lipoproteins and The Identification Of Apoa-imentioning
confidence: 99%